Efektivitas Terapi Relaksasi Benson Terhadap Kecemasan Lansia dengan Hipertensi - Ayu Dekawaty; Inne Yelisni (Ilmiah Institut Citra Internasional, 2023)
The elderly are individuals over the age of 60 who experience various biological and psychological changes. The increase in the number of the elderly presents various challenges to various aspects of life and health, such as the emergence of various genetic diseases. The decline in the function of body organs is characterized by the increasing susceptibility of the body to various diseases, one of which is hypertension causing emotional mental problems such as anxiety. Benson Relaxation Therapy is one of the nonfacological interventions that can be given to overcome anxiety, which consists of four basic components, namely a queit atmosphere, mental devices, passive attitudes, and a comfortable position. This study aims to determine the Effectiveness of Benson Relaxation Therapy against the anxiety of the elderly with hypertension at the Panti Lansia Harapan Kita. The research was conducted with a quasi-experimental design. Sample selection was carried out using the total sampling technique, as many as 18 respoden. Data analysis using the paired sample t-test obtained a p value of 0.000, which means that there is an effect of benson relaxation therapy on the anxiety of the elderly with hypertension before and after being given therapy. The results of this study are expected to be a referral source for nurses in providing interventions to the elderly with hypertension who experience anxiety.